Copper-based catalyst, preparation method and application thereof

By using a copper-based catalyst, combined with a silica support doped with zirconium silicate and an additive metal, the problem of poor catalyst stability is solved, and high-efficiency and low-cost indole synthesis is achieved, which is suitable for industrial applications.

CN119175101AActive Publication Date: 2024-12-24SHAANXI HYDROGEN ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411676394.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2024-12-24
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The existing catalysts for synthetic indole have poor stability and short service life, resulting in complex processes, high energy consumption and high cost, making it difficult to achieve industrial application.

Method used

Using a copper-based catalyst, the silicon dioxide support doped with zirconium silicate, copper as active components, and metals such as zinc, magnesium, yttrium, etc. are prepared by ball milling and impregnation precipitation to improve the stability of the catalyst and Anti-sintering ability.

Benefits of technology

The stability and service life of the catalyst are significantly improved, the continuous reaction yield is as high as more than 60%, the reaction yield is maintained at more than 40% for 200 hours, and the 500 hours yield is maintained at more than 32%, reducing costs and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119175101A_ABST
    Figure CN119175101A_ABST
Patent Text Reader

Abstract

The invention provides a copper-based catalyst, a preparation method and application thereof, and relates to the technical field of indole synthesis, the copper-based catalyst comprises a carrier, an active component and an auxiliary metal, the active component accounts for 5%-15% of the mass of the carrier, and the auxiliary metal accounts for 3%-15% of the mass of the carrier; wherein the carrier is a silicon dioxide carrier doped with zirconium silicate, and the doping amount of the zirconium silicate is 0-20% of the mass of the silicon dioxide carrier; the active component is copper; the auxiliary metal is composed of a first auxiliary metal and a second auxiliary metal in a mass ratio of (2-10): (1-5), the first auxiliary metal is one or more of zinc, magnesium, calcium, cobalt and nickel, and the second auxiliary metal is one or more of yttrium, lanthanum, cerium, praseodymium, samarium, aluminum, gallium, indium, chromium, molybdenum and tungsten. The copper-based catalyst provided by the embodiment of the invention is excellent in performance and has remarkable advantages in the aspect of continuous reaction life, the copper-based catalyst can continuously react for 10 hours during indole preparation, the yield is up to 60% or above, the yield is kept at 40% or above after the reaction is performed for 200 hours, and the yield is kept at 32% or above after the reaction is performed for 500 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthesizing indole, and in particular to a copper-based catalyst, a preparation method and application thereof. Background Art

[0002] With the rapid development of the hydrogen energy industry, organic liquid hydrogen storage as a major technical route will inevitably rise rapidly in many hydrogen storage and transportation solutions. The market demand for indole compounds as the main carrier of nitrogen heterocyclic hydrogen storage will inevitably increase by an order of magnitude. However, the current methods of synthesizing indole, such as separation and extraction, o-toluidine method, and Fischer method, all have the disadvantages of complex process, high energy consumption, high cost and high price, which is obviously not conducive to the large-scale promotion and application of organic liquids.

[0003] The one-step synthesis of indole from aniline and ethylene glycol using the alcoholamine method can solve the cost problem well, but the key to this technical route lies in catalyst development. There are many catalysts reported in relevant literature and patents. The main disadvantages are that the precious metal catalysts are expensive and complex in structure. At the same time, there are problems such as high reaction temperature, serious catalyst deactivation, unclear yield and selectivity advantages, and difficulty in achieving continuous operation. At present, none of them has been industrialized. At present, the mainstream research direction of the catalyst for synthesizing indole by the alcoholamine method is Cu / SiO2 catalyst with high yield, good selectivity and few by-products, in which SiO2 is used as a carrier, but the overall service life of the catalyst is not long and the stability is poor.

[0004] Therefore, in the field of indole synthesis technology, the poor stability and short service life of Cu / SiO2 catalysts have become technical problems that need to be solved urgently. Summary of the invention

[0005] To solve the above problems, in the first aspect, the present invention provides a copper-based catalyst, which is composed of a carrier, an active component and a promoter metal, wherein the active component accounts for 5% to 15% of the carrier mass, and the promoter metal accounts for 3% to 15% of the carrier mass; The carrier is a silica carrier doped with zirconium silicate, and the doping amount of the zirconium silicate is 0-20% of the mass of the silica carrier; the active component is copper; the auxiliary metal is a first auxiliary metal and a second auxiliary metal in a mass ratio of 2-10:1-5, the first auxiliary metal is one or more of zinc, magnesium, calcium, cobalt, and nickel, and the second auxiliary metal is one or more of yttrium, lanthanum, cerium, praseodymium, samarium, aluminum, gallium, indium, chromium, molybdenum, and tungsten.

[0006] Preferably, the doping amount of the zirconium silicate is 1-20% of the mass of the silica carrier.

[0007] Preferably, the first auxiliary agent is zinc and magnesium, and the second auxiliary agent is yttrium and cerium; the zinc accounts for 3% of the mass of the carrier, the magnesium accounts for 3% of the mass of the carrier, the yttrium accounts for 1% of the mass of the carrier, and the cerium accounts for 1% of the mass of the carrier; the active component accounts for 10% of the mass of the carrier; and the doping amount of the zirconium silicate is 10% of the mass of the silica carrier.

[0008] Preferably, the carrier is a silica carrier.

[0009] In a second aspect, the present invention provides a method for preparing the copper-based catalyst described in the first aspect, the preparation method comprising: S1, silicon dioxide and zirconium silicate are ball-milled at a ball-milling speed of 50 r / min to 200 r / min for 6 h to 18 h to obtain a carrier; wherein the zirconium silicate is 0 to 20% of the mass of the silicon dioxide; S2, adding a 0.2 mol / L to 2 mol / L copper nitrate solution to the carrier and stirring for 2 h to 4 h, adding a 0.2 mol / L to 2 mol / L auxiliary metal impregnation solution and continuing stirring for 2 h to 4 h, adjusting the pH value to 9 to 11 and aging for 12 h to 24 h, washing until the pH value of the supernatant is within the range of 7 to 8, and obtaining a solid; the auxiliary metal impregnation solution is a mixed salt solution containing a first auxiliary metal and a second auxiliary metal; S3, drying and calcining the solid in sequence to obtain a powdered copper-based catalyst.

[0010] Preferably, the pore size of the silica is in the range of 2 nm to 50 nm, and the specific surface area of ​​the silica is 200 m 2 / g~600 m 2 / g; the particle size of the zirconium silicate is less than 1.5 um.

[0011] Preferably, the mixed salt solution is a nitrate, chloride or acetate solution; The first auxiliary agent is one or more of zinc, magnesium, calcium, cobalt, and nickel, and the second auxiliary agent is one or more of yttrium, lanthanum, cerium, praseodymium, samarium, aluminum, gallium, indium, chromium, molybdenum, and tungsten.

[0012] Preferably, in S3, the drying temperature is 60°C to 100°C, and the drying time is 24 h; the roasting temperature is 400°C to 700°C, and the roasting time is 2 h to 8 h, and the roasting heating rate is 2°C·min -1 ~8 ℃·min -1 .

[0013] In a third aspect, the present invention provides an application of the copper-based catalyst described in the first aspect, wherein the copper-based catalyst is used in a reaction of synthesizing indole compounds or indole derivatives by an alcoholamine process.

[0014] Preferably, the application includes: The copper-based catalyst is reduced at a reduction temperature of 100° C. to 200° C. in an atmosphere with a hydrogen to nitrogen volume ratio of 1:4; Aniline and ethylene glycol are directly reacted using the reduced copper-based catalyst at a reaction temperature of 260°C to 350°C and a space velocity of 0.1 h -1 ~3.0 h -1 to obtain an indole compound or an indole derivative; wherein the molar ratio of aniline to ethylene glycol is 1:1 to 9:1.

[0015] When the raw materials are N-methylaniline and ethylene glycol, N-methylindole can be obtained by directly using the copper-based catalyst and process conditions; when the raw materials are N-ethylaniline and ethylene glycol, N-ethylindole can be obtained by directly using the copper-based catalyst and process conditions; when the raw materials are m-methylaniline and ethylene glycol, 4-methylindole and 6-methylindole can be obtained by directly using the copper-based catalyst and process conditions; when the raw materials are p-methylaniline and ethylene glycol, 5-methylindole can be obtained by directly using the copper-based catalyst and process conditions; when the raw materials are aniline and propylene glycol, 3-methylindole can be obtained by directly using the copper-based catalyst and process conditions; when the raw materials are aniline and 1,2-propylene glycol, 2-methylindole can be obtained by directly using the copper-based catalyst and process conditions.

[0016] Preferably, when the raw materials are aniline and propylene glycol, the molar ratio of aniline to ethylene glycol is 9:1, and the copper-based catalyst is directly used to react with hydrogen at a reaction temperature of 260°C and a space velocity of 3.0 h -1 The reaction was carried out under the conditions of , and 3-methylindole was obtained with a yield of 76.4% (based on glycerol).

[0017] Compared with the prior art, the present invention has the following advantages: The invention provides a copper-based catalyst, a preparation method and an application thereof, and relates to the technical field of synthesizing indole. The copper-based catalyst consists of a carrier, an active component and an auxiliary metal, wherein the active component accounts for 5% to 15% of the carrier mass, and the auxiliary metal accounts for 3% to 15% of the carrier mass; wherein the carrier is a silicon dioxide carrier doped with zirconium silicate, and the doping amount of zirconium silicate is 0 to 20% of the silicon dioxide carrier mass; the active component is copper; and the auxiliary metal consists of a first auxiliary metal and a second auxiliary metal in a mass ratio of 2 to 10:1 to 5, wherein the first auxiliary metal is one or more of zinc, magnesium, calcium, cobalt and nickel, and the second auxiliary metal is one or more of yttrium, lanthanum, cerium, praseodymium, samarium, aluminum, gallium, indium, chromium, molybdenum and tungsten. The copper-based catalyst provided in the embodiment of the present invention has excellent performance and has significant advantages in terms of sustained reaction life. When preparing indole, the copper-based catalyst can react continuously for 10 h with a yield of more than 60%, react for 200 h with a yield maintained at more than 40%, and react for 500 h with a yield maintained at more than 32%.

[0018] The copper-based catalyst provided in the embodiment of the present invention, on the one hand, introduces zirconium in a more stable and warmer manner, that is, by doping zirconium silicate into a silica carrier, which not only does not reduce the activity of the Cu / SiO2 catalyst, but on the contrary greatly improves the stability of the catalyst. The silica carrier doped with zirconium silicate can improve the stability of the Cu / SiO2 catalyst. The more stable it is, the higher its catalytic activity and the longer its life. On the other hand, the first auxiliary metal and the second auxiliary metal introduced not only jointly enhance the interaction between the active component copper and the carrier, but also jointly increase the dispersion of the active component copper, both of which are conducive to improving the anti-sintering ability of the active component copper, thereby enhancing the stability of the catalyst; specifically, the first auxiliary metal introduced forms an alloy with the active component copper, which can not only disperse the distance between the active component copper, thereby improving the dispersion of the active component copper on the surface of the silica carrier, so as to prevent the catalytic activity from being reduced due to aggregation during the indole synthesis reaction, and the copper-based catalyst is more fully exposed to the reaction during the indole synthesis reaction, thereby improving the stability and service life of the copper-based catalyst; and it can also enhance the interaction between the active component copper and the carrier, thereby inhibiting the sintering and agglomeration of the active component copper during the indole synthesis reaction, and reducing the carbon deposition of the catalyst. The second auxiliary metal introduced can not only affect the electron transfer, lattice distortion, and grain size of the active component copper, but also affect the acidity and alkalinity of the carrier surface and the surface structure, thereby jointly improving the activity and stability of the copper-based catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 This is a flow chart of a method for preparing a copper-based catalyst according to an embodiment of the present invention; Figure 2 This is a scanning electron microscope image of the copper-based catalyst obtained in Example 2 of the present invention; Figure 3 This is the pore size distribution diagram of the copper-based catalyst prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0021] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0022] Specific experimental steps or conditions are not specified in the embodiments, and the operations or conditions of the conventional experimental steps described in the prior art in the art can be carried out. The reagents used and other instruments that do not specify the manufacturer are all conventional reagent products that can be obtained commercially. In addition, the accompanying drawings are only schematic diagrams of the embodiments of the present disclosure and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated description will be omitted. Some block diagrams shown in the accompanying drawings are functional entities and do not necessarily correspond to physically or logically independent entities.

[0023] In order to extend the service life of the Cu / SiO2 catalyst, the inventor replaced the active component of the catalyst with ZrO2 to obtain a ZrO2 / SiO2 catalyst. Specifically, during the preparation, zirconium nitrate was first loaded on a SiO2 carrier, and then dried and calcined in sequence to obtain a ZrO2 / SiO2 catalyst; however, compared with the Cu / SiO2 catalyst, the ZrO2 / SiO2 catalyst had a lower yield and more by-products. Based on this, in order to extend the service life of the Cu / SiO2 catalyst, the inventor introduced zirconium into the Cu / SiO2 catalyst in the form of an auxiliary agent, but found that the auxiliary zirconium could not synergize with the main catalyst Cu to increase the service life or stability of the catalyst, but would significantly reduce the catalytic activity of the Cu / SiO2 catalyst. Therefore, it is very difficult to achieve a catalyst with both high catalytic activity and long life.

[0024] In view of this, the present invention changes the method of introducing zirconium into doping zirconium in the carrier and doping in the form of zirconium silicate, which not only does not reduce the activity of the Cu / SiO2 catalyst, but on the contrary greatly improves the stability of the catalyst; further, in order to improve the catalytic activity and life of the Cu / SiO2 catalyst doped with zirconium silicate in the SiO2 carrier, two different auxiliary metals are introduced at the same time, which on the one hand enhances the interaction between the active component copper and the carrier, and on the other hand increases the dispersion degree of the active component copper, both of which are beneficial to improving the anti-sintering ability of the active component copper and enhancing the stability of the catalyst.

[0025] In the first aspect, the present invention provides a copper-based catalyst, which consists of a carrier, an active component and a promoter metal, wherein the active component accounts for 5% to 15% of the carrier mass, and the promoter metal accounts for 3% to 15% of the carrier mass; wherein the carrier is a silica carrier doped with zirconium silicate, and the doping amount of the zirconium silicate is 0 to 20% of the mass of the silica carrier; the active component is copper; the promoter metal consists of a first promoter metal and a second promoter metal in a mass ratio of 2 to 10:1 to 5, wherein the first promoter metal is one or more of zinc, magnesium, calcium, cobalt, and nickel, and the second promoter metal is one or more of yttrium, lanthanum, cerium, praseodymium, samarium, aluminum, gallium, indium, chromium, molybdenum, and tungsten.

[0026] The copper-based catalyst provided in the embodiment of the present invention, on the one hand, introduces zirconium in a more stable and warmer manner, that is, by doping zirconium silicate in a silica carrier, which not only does not reduce the activity of the Cu / SiO2 catalyst, but on the contrary greatly improves the stability of the catalyst. The silica carrier doped with zirconium silicate can improve the stability of the Cu / SiO2 catalyst; on the other hand, the introduced first auxiliary metal and the second auxiliary metal not only jointly enhance the interaction between the active component copper and the carrier, but also jointly increase the dispersion of the active component copper. Both aspects are beneficial to improving the anti-sintering ability of the active component copper, thereby enhancing the stability of the catalyst. The more stable it is, the higher its catalytic activity and the longer its life.

[0027] Specifically, the first auxiliary metal introduced forms an alloy with the active component copper, which can disperse the distance between the active component copper, thereby improving the dispersion of the active component copper on the surface of the silica carrier to prevent the catalytic activity from decreasing due to aggregation during the indole synthesis reaction. The copper-based catalyst is more fully exposed to the reaction during the indole synthesis reaction, thereby improving the stability and service life of the copper-based catalyst; on the other hand, it can also enhance the interaction between the active component copper and the carrier, thereby inhibiting the sintering and agglomeration of the active component copper during the indole synthesis reaction and reducing the carbon deposition of the catalyst. The second auxiliary metal introduced can not only affect the electron transfer, lattice distortion, and grain size of the active component copper, but also affect the acidity and alkalinity of the carrier surface and the surface structure, thereby jointly improving the activity and stability of the copper-based catalyst.

[0028] The copper-based catalyst provided in the embodiment of the present invention has excellent performance and has significant advantages in terms of sustained reaction life. When preparing indole, the copper-based catalyst can react continuously for 10 hours with a yield of more than 60%, react for 200 hours with a yield maintained at more than 40%, and react for 500 hours with a yield maintained at more than 32%.

[0029] In addition, since the raw materials of the copper-based catalyst provided in the embodiment of the present invention do not contain precious metals, its main components copper and silicon dioxide are inexpensive and are common chemical raw materials, and have the characteristics of low cost and large-scale production and application.

[0030] In some embodiments of the present invention, the doping amount of the zirconium silicate is 1-20% of the mass of the silica carrier.

[0031] In some embodiments of the present invention, the first auxiliary agent is zinc and magnesium, and the second auxiliary agent is yttrium and cerium; the zinc accounts for 3% of the mass of the carrier, the magnesium accounts for 3% of the mass of the carrier, the yttrium accounts for 1% of the mass of the carrier, and the cerium accounts for 1% of the mass of the carrier; the active component accounts for 10% of the mass of the carrier; and the doping amount of the zirconium silicate is 10% of the mass of the silica carrier.

[0032] The copper-based catalyst provided in this embodiment has a more significant advantage in terms of sustained reaction life. The yield is as high as 64.1% after a sustained reaction of 10 h, the yield is maintained at 55.5% after a reaction of 200 h, and the yield is maintained at more than 38.9% after a reaction of 500 h.

[0033] In some embodiments of the present invention, the support is a silica support.

[0034] In a second aspect, the present invention provides a method for preparing the copper-based catalyst described in the first aspect, the preparation method comprising: S1, silicon dioxide and zirconium silicate are ball-milled at a ball-milling speed of 50 r / min to 200 r / min for 6 h to 18 h to obtain a carrier; wherein the zirconium silicate is 0 to 20% of the mass of the silicon dioxide; S2, adding a 0.2 mol / L to 2 mol / L copper nitrate solution to the carrier and stirring for 2 h to 4 h, adding a 0.2 mol / L to 2 mol / L auxiliary metal impregnation solution and continuing stirring for 2 h to 4 h, adjusting the pH value to 9 to 11 and aging for 12 h to 24 h, washing until the pH value of the supernatant is within the range of 7 to 8, and obtaining a solid; the auxiliary metal impregnation solution is a mixed salt solution containing a first auxiliary metal and a second auxiliary metal; S3, drying and calcining the solid in sequence to obtain a powdered copper-based catalyst.

[0035] Specifically, in S2, the preparation process of the copper nitrate solution is as follows: weigh a certain amount of copper nitrate trihydrate Cu(NO3)2·3H2O, add it to 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; in S2, the preparation process of the auxiliary metal impregnation solution is as follows: weigh a certain amount of the first auxiliary metal and the second auxiliary metal, add them to 100 mL of deionized water and stir until they are completely dissolved to obtain an auxiliary metal impregnation solution; in S2, adjust its pH value to 9~11, and the regulator used is one or more of Na2CO3 solution, NaOH solution, and NH3·H2O solution; in S3, grind the dried solid until it has no granular feeling, put it into a porcelain boat, and then place it in a muffle furnace for roasting.

[0036] The embodiment of the present invention uses the simplest impregnation precipitation method to achieve doping of the carrier and the introduction of the first auxiliary metal and the second auxiliary metal. The copper-based catalyst obtained by the preparation method not only has excellent performance, but also has comprehensive performance that can reach the level of industrial production application, and is low in cost and suitable for large-scale production application. In addition, since the preparation method provided by the embodiment of the present invention has a simple process and a mature and reliable process route, the product differences between different batches obtained by the preparation method are small and the product performance is stable.

[0037] Specifically, zirconium silicate is first doped into a silica carrier by dry ball milling; the obtained carrier is then contacted with an additive metal impregnation solution and a copper nitrate solution, so that the active component copper, the first additive metal and the second additive metal are adsorbed on the carrier; finally, the copper-based catalyst is obtained through drying and calcination.

[0038] In some embodiments of the present invention, the pore size of the silica is in the range of 2 nm to 50 nm, and the specific surface area of ​​the silica is 200 m 2 / g~600 m 2 / g; the particle size of the zirconium silicate is less than 1.5 um.

[0039] In some embodiments of the present invention, the mixed salt solution is a nitrate, chloride or acetate solution; the first auxiliary agent is one or more of zinc, magnesium, calcium, cobalt, and nickel; and the second auxiliary agent is one or more of yttrium, lanthanum, cerium, praseodymium, samarium, aluminum, gallium, indium, chromium, molybdenum, and tungsten.

[0040] In some embodiments of the present invention, in S3, the drying temperature is 60°C to 100°C, and the drying time is 24 h; the roasting temperature is 400°C to 700°C, and the roasting time is 2 h to 8 h, and the roasting heating rate is 2°C·min -1 ~8 ℃·min -1 .

[0041] Furthermore, the drying temperature was 80 °C, the calcination temperature was 600 °C, the calcination time was 8 h, and the calcination heating rate was 5 °C·min -1 .

[0042] In a third aspect, the present invention provides an application of the copper-based catalyst described in the first aspect, wherein the copper-based catalyst is used in a reaction of synthesizing indole compounds or indole derivatives by an alcoholamine process.

[0043] The principle of synthesizing indole based on the alcoholamine method is different from the principle of synthesizing indole by other methods. Therefore, the catalytic effect of the copper-based catalyst provided by the present invention is only for the synthesis of indole from aniline and ethylene glycol. The copper-based catalyst is used for the synthesis of indole compounds, such as indole, 3-methylindole, N-methylindole, etc., and can also be used for the preparation of indole derivatives.

[0044] When the copper-based catalyst provided in the embodiment of the present invention is used for synthesizing indole by the alcoholamine method, it has a long continuous reaction life. The yield of the copper-based catalyst is as high as 60% or more after continuous reaction for 10 hours, the yield is maintained at more than 40% after reaction for 200 hours, and the yield is maintained at more than 32% after reaction for 500 hours, which has good industrial application prospects.

[0045] In some embodiments of the present invention, the application includes: The copper-based catalyst is reduced at a reduction temperature of 100° C. to 200° C. in an atmosphere with a hydrogen to nitrogen volume ratio of 1:4; Aniline and ethylene glycol are directly reacted using the reduced copper-based catalyst at a reaction temperature of 260°C to 350°C and a space velocity of 0.1 h -1 ~3.0 h -1to obtain an indole compound or an indole derivative; wherein the molar ratio of aniline to ethylene glycol is 1:1 to 9:1.

[0046] Specifically, the reduction is to reduce the copper in the copper-based catalyst to elemental copper to release the elemental copper, which is an active site. Therefore, during the reaction of aniline and ethylene glycol, the elemental copper can well promote the reaction. When the copper-based catalyst is reduced, until there is no obvious water vapor in the outlet gas, it indicates that the reduction is completed, thereby completing the activation of the copper-based catalyst.

[0047] In this embodiment, since the first auxiliary metal and the second auxiliary metal are introduced into the copper-based catalyst, even if the elemental copper is completely released before synthesizing indole, the elemental copper will not agglomerate or sinter during the reduction process, and thus the catalytic activity of the copper-based catalyst will not be affected after the reduction is completed.

[0048] In order to enable those skilled in the art to better understand the present invention, the preparation method provided by the present invention is described below through multiple specific examples.

[0049] Comparative Example 1 Weigh 50 g of silica and place it in a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls. After ball milling at a speed of 100 r / min for 10 h, take out the obtained silica carrier and sieve it for later use. Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add 100 mL of deionized water and stir until completely dissolved to obtain a copper nitrate solution; add the copper nitrate solution dropwise to the obtained silica carrier, stir for 2 h, then add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8 to obtain a solid.

[0050] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C min. -1 , to obtain a powdered catalyst.

[0051] 3 g of the catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150°C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 300°C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h -1 ,The evaluation conditions and results are shown in Table 1.

[0052] Comparative Example 2 Weigh 50 g of silica and place it in a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls. After ball milling at a speed of 100 r / min for 10 h, take out the obtained silica carrier and sieve it for later use. Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it to 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 11.74 g of zirconium nitrate pentahydrate Zr(NO3)4·5H2O, an auxiliary metal, add it to 100 mL of deionized water and stir until it is completely dissolved to obtain an auxiliary impregnation solution; add the copper nitrate solution dropwise to the obtained silica carrier, stir for 3 h, then add the auxiliary impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, and wash until the pH value of the supernatant is in the range of 7-8 to obtain a solid.

[0053] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C·min -1 , to obtain a powdered catalyst.

[0054] 3 g of the catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150°C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 300°C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h -1 ,The evaluation conditions and results are shown in Table 1.

[0055] It can be seen from Table 1 that after zirconium is introduced into the Cu / SiO2 catalyst in the form of an additive, the additive zirconium cannot synergize with the main catalyst Cu to improve the service life or stability of the catalyst, but will significantly reduce the catalytic activity of the Cu / SiO2 catalyst.

[0056] Example 1 Weigh 50 g of silica and place it in a 500 mL ball mill. Add 200 mL of 10 mm diameter zirconium balls. After ball milling at a speed of 100 r / min for 10 h, take out the obtained carrier and sieve it for later use. Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it into 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 6.85 g of zinc nitrate hexahydrate Zn(NO3)2·6H2O and 16 g of magnesium nitrate hexahydrate Mg(NO3)2·6H2O as the first auxiliary metal, weigh 2.15 g of yttrium nitrate hexahydrate Y(NO3)3·6H2O and 1.55 g of cerium nitrate hexahydrate Ce(NO3)3·6H2O as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal into 100 mL of deionized water and stir until it is completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, wash until the pH value of the supernatant is in the range of 7-8, and obtain a solid.

[0057] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C min. -1 , a powdered copper-based catalyst was obtained.

[0058] 3 g of copper-based catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150 °C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 300 °C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h -1 ,The evaluation conditions and results are shown in Table 1.

[0059] Example 2 Weigh 45 g of silicon dioxide and 5 g of zirconium silicate into a 500 mL ball mill, add 200 mL of 10 mm diameter zirconium balls, and mill at a speed of 100 r / min for 10 h. Take out the carrier and sieve it for later use. Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it into 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 6.85 g of zinc nitrate hexahydrate Zn(NO3)2·6H2O and 16 g of magnesium nitrate hexahydrate Mg(NO3)2·6H2O as the first auxiliary metal, weigh 2.15 g of yttrium nitrate hexahydrate Y(NO3)3·6H2O and 1.55 g of cerium nitrate hexahydrate Ce(NO3)3·6H2O as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal into 100 mL of deionized water and stir until it is completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, wash until the pH value of the supernatant is in the range of 7-8, and obtain a solid.

[0060] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C min. -1 , a powdered copper-based catalyst was obtained.

[0061] The copper-based catalyst of this embodiment was tested and characterized. Figure 2 and Figure 3 As shown, Figure 2 This is a scanning electron microscope image of the copper-based catalyst obtained in Example 1 of the present invention; Figure 3 This is the pore size distribution diagram of the copper-based catalyst prepared in Example 1 of the present invention.

[0062] 3 g of copper-based catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150 °C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 300 °C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h -1 ,The evaluation conditions and results are shown in Table 1.

[0063] Example 3 Weigh 40 g of silicon dioxide and 10 g of zirconium silicate and place them in a 500 mL ball mill. Add 200 mL of zirconium balls with a diameter of 10 mm. After ball milling at a speed of 100 r / min for 10 h, take out the obtained carrier and sieve it for later use. Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it into 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 6.85 g of zinc nitrate hexahydrate Zn(NO3)2·6H2O and 16 g of magnesium nitrate hexahydrate Mg(NO3)2·6H2O as the first auxiliary metal, weigh 2.15 g of yttrium nitrate hexahydrate Y(NO3)3·6H2O and 1.55 g of cerium nitrate hexahydrate Ce(NO3)3·6H2O as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal into 100 mL of deionized water and stir until it is completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, wash until the pH value of the supernatant is in the range of 7-8, and obtain a solid.

[0064] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C min. -1 , a powdered copper-based catalyst was obtained.

[0065] 3 g of copper-based catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150 °C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 300 °C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h -1 ,The evaluation conditions and results are shown in Table 1.

[0066] Example 4 Weigh 45 g of silicon dioxide and 5 g of zirconium silicate into a 500 mL ball mill, add 200 mL of 10 mm diameter zirconium balls, and mill at a speed of 100 r / min for 10 h. Take out the carrier and sieve it for later use. Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it into 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 2.28 g of zinc nitrate hexahydrate Zn(NO3)2·6H2O and 5.33 g of magnesium nitrate hexahydrate Mg(NO3)2·6H2O, weigh 1.08 g of yttrium nitrate hexahydrate Y(NO3)3·6H2O and 0.78 g of cerium nitrate hexahydrate Ce(NO3)3·6H2O, add the weighed first and second auxiliary metals into 100 mL of deionized water and stir until they are completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, wash until the pH value of the supernatant is in the range of 7-8, and obtain a solid.

[0067] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C·min -1 , a powdered copper-based catalyst was obtained.

[0068] 3 g of copper-based catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150 °C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 300 °C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h -1 ,The evaluation conditions and results are shown in Table 1.

[0069] Example 5 Weigh 45 g of silicon dioxide and 5 g of zirconium silicate into a 500 mL ball mill, add 200 mL of 10 mm diameter zirconium balls, and mill at a speed of 100 r / min for 10 h. Take out the carrier and sieve it for later use. Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it to 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 11.42 g of zinc nitrate hexahydrate Zn(NO3)2·6H2O and 26.67 g of magnesium nitrate hexahydrate Mg(NO3)2·6H2O, weigh the second auxiliary metal 5.38 g of yttrium nitrate hexahydrate Y(NO3)3·6H2O and 3.88 g of cerium nitrate hexahydrate Ce(NO3)3·6H2O, add the weighed first auxiliary metal and the second auxiliary metal to 100 mL of deionized water and stir until it is completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, wash until the pH value of the supernatant is in the range of 7-8, and obtain a solid.

[0070] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then, it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C min. -1 , a powdered copper-based catalyst was obtained.

[0071] 3 g of copper-based catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150 °C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 300 °C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h -1 ,The evaluation conditions and results are shown in Table 1.

[0072] Example 6 Weigh 45 g of silicon dioxide and 5 g of zirconium silicate into a 500 mL ball mill, add 200 mL of 10 mm diameter zirconium balls, and mill at a speed of 100 r / min for 10 h. Take out the carrier and sieve it for later use. Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it into 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 17.7 g of calcium nitrate tetrahydrate Ca(NO3)2·4H2O as the first auxiliary metal, weigh 4.67 g of lanthanum nitrate hexahydrate La(NO3)3·6H2O as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal into 100 mL of deionized water and stir until it is completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, wash until the pH value of the supernatant is in the range of 7-8, and obtain a solid.

[0073] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C·min -1 , a powdered copper-based catalyst was obtained.

[0074] 3 g of copper-based catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150 °C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 300 °C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h -1 ,The evaluation conditions and results are shown in Table 1.

[0075] Example 7 Weigh 45 g of silicon dioxide and 5 g of zirconium silicate into a 500 mL ball mill, add 200 mL of 10 mm diameter zirconium balls, and mill at a speed of 100 r / min for 10 h. Take out the carrier and sieve it for later use. Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it into 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 17.7 g of calcium nitrate tetrahydrate Ca(NO3)2·4H2O as the first auxiliary metal, weigh 11.54 g of chromium nitrate nonahydrate Cr(NO3)3·9H2O as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal into 100 mL of deionized water and stir until it is completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, wash until the pH value of the supernatant is in the range of 7-8, and obtain a solid.

[0076] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C·min -1 , a powdered copper-based catalyst was obtained.

[0077] 3 g of copper-based catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150 °C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 300 °C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h -1 ,The evaluation conditions and results are shown in Table 1.

[0078] Example 8 Weigh 45 g of silicon dioxide and 5 g of zirconium silicate into a 500 mL ball mill, add 200 mL of 10 mm diameter zirconium balls, and mill at a speed of 100 r / min for 10 h. Take out the carrier and sieve it for later use. Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it into 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 17.7 g of calcium nitrate tetrahydrate Ca(NO3)2·4H2O as the first auxiliary metal, weigh 20.83 g of aluminum nitrate nonahydrate Al(NO3)3·9H2O as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal into 100 mL of deionized water and stir until they are completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, wash until the pH value of the supernatant is in the range of 7-8, and obtain a solid.

[0079] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C·min -1 , a powdered copper-based catalyst was obtained.

[0080] 3 g of copper-based catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150 °C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 300 °C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h-1 ,The evaluation conditions and results are shown in Table 1.

[0081] Example 9 Weigh 45 g of silicon dioxide and 5 g of zirconium silicate into a 500 mL ball mill, add 200 mL of 10 mm diameter zirconium balls, and mill at a speed of 100 r / min for 10 h. Take out the carrier and sieve it for later use. Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it into 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 12.33 g of cobalt nitrate hexahydrate Co(NO3)2·6H2O and 7.4 g of nickel nitrate hexahydrate Ni(NO3)2·6H2O, weigh 3.12 g of lanthanum nitrate hexahydrate La(NO3)3·6H2O and 3.85 g of chromium nitrate nonahydrate Cr(NO3)3·9H2O, add the weighed first and second auxiliary metals into 100 mL of deionized water and stir until they are completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, wash until the pH value of the supernatant is in the range of 7-8, and obtain a solid.

[0082] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C·min -1 , a powdered copper-based catalyst was obtained.

[0083] 3 g of copper-based catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150 °C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 300 °C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h -1 ,The evaluation conditions and results are shown in Table 1.

[0084] Example 10 Weigh 45 g of silicon dioxide and 5 g of zirconium silicate into a 500 mL ball mill, add 200 mL of 10 mm diameter zirconium balls, and mill at a speed of 100 r / min for 10 h. Take out the carrier and sieve it for later use. Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it into 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 7.4 g of cobalt nitrate hexahydrate Co(NO3)2·6H2O and 12.33 g of nickel nitrate hexahydrate Ni(NO3)2·6H2O, weigh 1.56 g of lanthanum nitrate hexahydrate La(NO3)3·6H2O and 13.89 g of aluminum nitrate nonahydrate Al(NO3)3·9H2O, add the weighed first and second auxiliary metals into 100 mL of deionized water and stir until they are completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, wash until the pH value of the supernatant is in the range of 7-8, and obtain a solid.

[0085] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C·min -1 , a powdered copper-based catalyst was obtained.

[0086] 3 g of copper-based catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150 °C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 300 °C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h -1 ,The evaluation conditions and results are shown in Table 1.

[0087] Embodiment 11 Weigh 45 g of silicon dioxide and 5 g of zirconium silicate into a 500 mL ball mill, add 200 mL of 10 mm diameter zirconium balls, and mill at a speed of 100 r / min for 10 h. Take out the carrier and sieve it for later use. Weigh 9.45 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it to 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 6.85 g of zinc nitrate hexahydrate Zn(NO3)2·6H2O and 16 g of magnesium nitrate hexahydrate Mg(NO3)2·6H2O as the first auxiliary metal, weigh 2.15 g of yttrium nitrate hexahydrate Y(NO3)3·6H2O and 1.55 g of cerium nitrate hexahydrate Ce(NO3)3·6H2O as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal to 100 mL of deionized water and stir until it is completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, wash until the pH value of the supernatant is in the range of 7-8, and obtain a solid.

[0088] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C·min -1 , a powdered copper-based catalyst was obtained.

[0089] 3 g of copper-based catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150 °C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 300 °C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h -1 ,The evaluation conditions and results are shown in Table 1.

[0090] Example 12 Weigh 45 g of silicon dioxide and 5 g of zirconium silicate into a 500 mL ball mill, add 200 mL of 10 mm diameter zirconium balls, and mill at a speed of 100 r / min for 10 h. Take out the carrier and sieve it for later use. Weigh 28.36 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it into 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 6.85 g of zinc nitrate hexahydrate Zn(NO3)2·6H2O and 16 g of magnesium nitrate hexahydrate Mg(NO3)2·6H2O as the first auxiliary metal, weigh 2.15 g of yttrium nitrate hexahydrate Y(NO3)3·6H2O and 1.55 g of cerium nitrate hexahydrate Ce(NO3)3·6H2O as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal into 100 mL of deionized water and stir until it is completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, wash until the pH value of the supernatant is in the range of 7-8, and obtain a solid.

[0091] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C·min -1 , a powdered copper-based catalyst was obtained.

[0092] 3 g of copper-based catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150 °C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 300 °C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h -1 ,The evaluation conditions and results are shown in Table 1.

[0093] Embodiment 13 Weigh 45 g of silicon dioxide and 5 g of zirconium silicate into a 500 mL ball mill, add 200 mL of 10 mm diameter zirconium balls, and mill at a speed of 100 r / min for 10 h. Take out the carrier and sieve it for later use. Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it into 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 6.85 g of zinc nitrate hexahydrate Zn(NO3)2·6H2O and 16 g of magnesium nitrate hexahydrate Mg(NO3)2·6H2O as the first auxiliary metal, weigh 2.15 g of yttrium nitrate hexahydrate Y(NO3)3·6H2O and 1.55 g of cerium nitrate hexahydrate Ce(NO3)3·6H2O as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal into 100 mL of deionized water and stir until it is completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, wash until the pH value of the supernatant is in the range of 7-8, and obtain a solid.

[0094] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C·min -1 , a powdered copper-based catalyst was obtained.

[0095] 3 g of copper-based catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150 °C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 280 °C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h -1 ,The evaluation conditions and results are shown in Table 1.

[0096] Embodiment 14 Weigh 45 g of silicon dioxide and 5 g of zirconium silicate into a 500 mL ball mill, add 200 mL of 10 mm diameter zirconium balls, and mill at a speed of 100 r / min for 10 h. Take out the carrier and sieve it for later use. Weigh 18.91 g of copper nitrate trihydrate Cu(NO3)2·3H2O, add it into 100 mL of deionized water and stir until it is completely dissolved to obtain a copper nitrate solution; weigh 6.85 g of zinc nitrate hexahydrate Zn(NO3)2·6H2O and 16 g of magnesium nitrate hexahydrate Mg(NO3)2·6H2O as the first auxiliary metal, weigh 2.15 g of yttrium nitrate hexahydrate Y(NO3)3·6H2O and 1.55 g of cerium nitrate hexahydrate Ce(NO3)3·6H2O as the second auxiliary metal, add the weighed first auxiliary metal and the second auxiliary metal into 100 mL of deionized water and stir until it is completely dissolved to obtain an auxiliary metal impregnation solution; add the copper nitrate solution dropwise to the obtained carrier, stir for 3 h, then add the auxiliary metal impregnation solution, continue stirring for 3 h, add sodium carbonate Na2CO3 solution to adjust the pH value to 9-11, age for 12 h, wash until the pH value of the supernatant is in the range of 7-8, and obtain a solid.

[0097] The solid was placed in a glass watch glass and dried in a vacuum oven at 80 °C for 24 h. The dried solid was ground until there was no granularity. Then it was placed in a porcelain boat and calcined in a muffle furnace at 600 °C for 8 h at a heating rate of 5 °C·min -1 , a powdered copper-based catalyst was obtained.

[0098] 3 g of copper-based catalyst was loaded into the reactor for reduction, with a hydrogen to nitrogen volume ratio of 1:4 and a reduction temperature of 150 °C. The reduction was completed when there was no obvious water vapor in the outlet gas. The reduced copper-based catalyst was used to react aniline with ethylene glycol to generate indole. When the temperature was raised to 350 °C, the raw materials were added for reaction, with a molar ratio of ethylene glycol to aniline of 1:7 and a space velocity of 0.5 h -1 ,The evaluation conditions and results are shown in Table 1.

[0099] Table 1 Comparative Examples and Test Results

[0100] It can be seen that Example 1 uses a simple first auxiliary metal and a second auxiliary metal to modify the catalyst. Although the stability of the catalyst is improved after the improvement, specifically, the yield at the 200th hour is increased from about 10% to about 49%, and the yield at the 500th hour is increased from less than 5% to about 22%. Example 2 is based on Example 1, and an appropriate amount of zirconium silicate is further doped in the carrier. From the test results in Table 1, it can be seen that the copper-based catalyst of Example 1 decreases more and more as the reaction time of synthesizing indole increases; the copper-based catalyst obtained in Example 2 has a significant improvement in stability, specifically, the yield at the 200th hour is increased from about 10% to about 55%, and the yield at the 500th hour is increased from less than 5% to about 39%. In all examples, Example 2 shows the advantage of the best lifespan; and similar effects also appear in the catalysts from Example 3 to Example 14, and their stability is significantly improved.

[0101] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification.

[0102] For the method embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the order of the actions described, because according to the present invention, some steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and components involved are not necessarily required by the present invention.

[0103] The above is a detailed introduction to a copper-based catalyst, a preparation method and an application thereof provided by the present invention. Specific examples are used herein to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for a person skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation mode and the scope of application. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A copper-based catalyst, characterized in that The copper-based catalyst is composed of a carrier, an active component and a promoter metal, wherein the active component accounts for 5% to 15% of the carrier mass, and the promoter metal accounts for 3% to 15% of the carrier mass; The carrier is a silica carrier doped with zirconium silicate, and the doping amount of the zirconium silicate is 0-20% of the mass of the silica carrier; the active component is copper; the auxiliary metal is a first auxiliary metal and a second auxiliary metal in a mass ratio of 2-10:1-5, the first auxiliary metal is one or more of zinc, magnesium, calcium, cobalt, and nickel, and the second auxiliary metal is one or more of yttrium, lanthanum, cerium, praseodymium, samarium, aluminum, gallium, indium, chromium, molybdenum, and tungsten.

2. The copper-based catalyst according to claim 1, characterized in that The doping amount of the zirconium silicate is 1-20% of the mass of the silica carrier.

3. The copper-based catalyst according to claim 1, characterized in that The first auxiliary agent is zinc and magnesium, and the second auxiliary agent is yttrium and cerium; the zinc accounts for 3% of the mass of the carrier, the magnesium accounts for 3% of the mass of the carrier, the yttrium accounts for 1% of the mass of the carrier, and the cerium accounts for 1% of the mass of the carrier; the active component accounts for 10% of the mass of the carrier; and the doping amount of the zirconium silicate is 10% of the mass of the silica carrier.

4. The copper-based catalyst according to claim 1, characterized in that The carrier is a silica carrier.

5. A method for preparing the copper-based catalyst according to any one of claims 1 to 4, characterized in that: The preparation method comprises: S1, silicon dioxide and zirconium silicate are ball-milled at a ball-milling speed of 50 r / min to 200 r / min for 6 h to 18 h to obtain a carrier; wherein the zirconium silicate is 0 to 20% of the mass of the silicon dioxide; S2, adding a 0.2 mol / L to 2 mol / L copper nitrate solution to the carrier and stirring for 2 h to 4 h, adding a 0.2 mol / L to 2 mol / L auxiliary metal impregnation solution and continuing stirring for 2 h to 4 h, adjusting the pH value to 9 to 11 and aging for 12 h to 24 h, washing until the pH value of the supernatant is within the range of 7 to 8, and obtaining a solid; the auxiliary metal impregnation solution is a mixed salt solution containing a first auxiliary metal and a second auxiliary metal; S3, drying and calcining the solid in sequence to obtain a powdered copper-based catalyst.

6. The preparation method according to claim 5, characterized in that: The pore size of the silica is in the range of 2 nm to 50 nm, and the specific surface area of ​​the silica is 200 m 2 / g~600 m 2 / g; the particle size of the zirconium silicate is less than 1.5 um.

7. The preparation method according to claim 5, characterized in that: The mixed salt solution is a nitrate, chloride or acetate solution; The first auxiliary agent is one or more of zinc, magnesium, calcium, cobalt, and nickel, and the second auxiliary agent is one or more of yttrium, lanthanum, cerium, praseodymium, samarium, aluminum, gallium, indium, chromium, molybdenum, and tungsten.

8. The preparation method according to claim 5, characterized in that: In S3, the drying temperature is 60°C to 100°C, and the drying time is 24 h; the roasting temperature is 400°C to 700°C, and the roasting time is 2 h to 8 h, and the roasting heating rate is 2°C·min -1 ~8 ℃·min -1 .

9. Use of the copper-based catalyst according to any one of claims 1 to 4, characterized in that: The copper-based catalyst is used in the reaction of synthesizing indole compounds or indole derivatives by alcoholamine method.

10. The use according to claim 9, characterized in that: The applications include: The copper-based catalyst is reduced at a reduction temperature of 100° C. to 200° C. in an atmosphere with a hydrogen to nitrogen volume ratio of 1:4; Aniline and ethylene glycol are directly reacted using the reduced copper-based catalyst at a reaction temperature of 260°C to 350°C and a space velocity of 0.1 h -1 ~3.0 h -1 to obtain an indole compound or an indole derivative; wherein the molar ratio of aniline to ethylene glycol is 1:1 to 9:1.

Citation Information

Patent Citations

  • Catalyst for synthesizing 3-methylindole through stationary bed by using glycerin as raw material

    CN103464158A

  • Copper-silicon catalyst as well as preparation method and application thereof

    CN113522261A

  • Method and system for synthesizing indole and derivatives thereof by alcohol amine method

    CN118546083A